2019
DOI: 10.1016/j.matchemphys.2018.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal effect of magnesium ions over planktonic and sessile Staphylococcus epidermidis and Escherichia coli

Abstract: Magnesium and its alloys are in focus to produce implants due to their excellent mechanical properties, facility to decompose in the body, enhancement of new bone formation and antibacterial properties. However, there is still a lack of consensus about the origin of such antibacterial effect. Up to date, most antibacterial studies were performed over newly synthesized MgO particles, nanotubes or nanowires in the form of slurries, integrated within polymeric matrixes or as coatings of other bulk materials where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 50 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…Although magnesium is an essential ion for the enzymes activity and can enhance coating formation on bacterial biofilms, it has also interesting properties against bacteria contamination [20][21][22][23]. The mechanisms behind this antibacterial effect are the alkalinization of the surrounding media and the great osmotic stress originated on the cells by the ingestion of magnesium ions [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Although magnesium is an essential ion for the enzymes activity and can enhance coating formation on bacterial biofilms, it has also interesting properties against bacteria contamination [20][21][22][23]. The mechanisms behind this antibacterial effect are the alkalinization of the surrounding media and the great osmotic stress originated on the cells by the ingestion of magnesium ions [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The multicomponent composition of the considered systems containing the magnesium alloy plate and PBS or bacterial dispersion in PBS, with the products of chemical interaction between the magnesium and the liquid phase, did not allow for unambiguously relating the pH of the liquid medium with the concentration of magnesium ions. At the same time, the ion concentration was considered as one of the determining factors for the bactericidal action of metals for bacterial cells, both planktonic and deposited onto the substrate [ 20 , 30 , 31 , 32 ]. For example, the bactericidal effects of magnesium ions and the solution pH were differentiated in [ 32 ], and it was shown that a higher concentration of magnesium ions resulted in a more intense bactericidal effect, which the authors had related to the larger osmotic stresses exerted on the cells.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the increase in the concentration of Mg 2+ is accompanied by a stronger antibacterial effect. The observed phenomena were explained by the large osmotic stress damaging the cell’s wall, yielded by the higher concentration of Mg ions [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its rapid corrosion increases the concentration of magnesium ions locally, which alters the pH value and prohibits bacterial activities in vivo [70]. Though recent studies have further confirmed the significant antibacterial effect of magnesium ions on Staphylococcus epidermidis and Escherichia coli (E. coli) [71], it is essential to note that with biofilms, bacteria can withstand external pH alterations and continue infecting the tissues [68].…”
Section: Anti-microbial Strategiesmentioning
confidence: 99%